Openspace Ventures: Sustainable Venture Capital - DEARTH, Matt (Institutional Knowledge at Singapore Management University, 2022)
The case describes a successful Singapore-based venture capital (VC) firm, Openspace Ventures, and its decision to incorporate elements of sustainable investing throughout its business. Similar to many early-stage investors, Openspace’s early returns were driven by portfolio companies with a combination of large addressable markets, dedicated entrepreneurs, and a strong product offering aligned with the opportunity. Issues of sustainability or environmental, social, and (corporate) governance (ESG) were not initially part of their process, but after their initial success the founders are interested in “doing well by doing good”—and believe that it will not require sacrificing returns. This case illustrates how traditional early-stage investors such as Openspace can evaluate the trade-offs associated with adding a sustainability component to their investment process. In this brief case we introduce the protagonists, Shane Chesson, his co-founder Hian Goh, and the proposal they deliver to a room full of investors: to integrate sustainable investing principles throughout their successful, traditional VC business. Class discussion should lead to a decision on whether Openspace should proceed with Openhand, and if so, how to successfully manage the implementation. Students will be able to 1) apply knowledge of the relationship between VC and sustainable investing to other asset classes or strategies experiencing a similar transition; 2) address the potential concerns of various stakeholders of a VC firm related to the impact of a shift towards sustainable investing; 3) Understand the challenges associated with changing perception and practice in early-stage investing, both internally and externally; 4) appreciate how motivated leadership can incorporate sustainability into VC without relying on concessions.